La Gamificación en el proceso de enseñanza-aprendizaje de los estudiantes de 7mo año de E.G.B., de la Unidad Educativa “Madre Gertrudis”, Cevallos-Tungurahua, periodo 2020-2021 - Pico Mejía, Deisy Yessenia (2022)
Despite the technological advances brought about by the 21st century and the changes that have taken place in the educational field, these continue to be limited and insufficient since most processes are based on a traditional model in which the main protagonists are notebooks, books, and theory. This research aims to reveal the changes obtained by applying the Gamification technique as an alternative for improvement and innovation in the teaching-learning processes. It is a study based on a mixed approach, taking the scientific method as a basis. It is based on the premise that teachers do not apply innovative strategies in the development of their teaching due to a lack of training and lack of knowledge of techniques such as Gamification, wasting the benefits offered by technology. In order to gather information, it worked with 22 students corresponding to the 7th year of BGE to whom a survey was applied, which addressed data when subjected to analysis, allowed us to conclude that it is an effective technique to awaken and maintain the interest and motivation of students and thus carry out meaningful, participatory learning that reveals the importance and the need to support the PEA with innovative strategies, techniques, and methodologies. Several gamification activities are presented in this research work, which facilitates the teaching-learning process. Taking into account that each student is different, it has proposed activities that attract the attention of each one of them, and this, in turn, helps the acquisition of knowledge in an effective way.